National Association of Medical Examiners Position Paper: Recommendations for the Definition, Investigation, Postmortem Examination, and Reporting of Deaths in Custody. Issue 4 (December 2017) - Mitchell, Roger A.; Diaz, Francisco; Goldfogel, Gary A.; Fajardo, Mark; Fiore, Stephany E.; Henson, Tanisha V.; Jorden, Michelle A.; Kelly, Sean; Luzi, Scott; Quinn, Megan; Wolf, Dwayne A.
The National Association of Medical Examiners commissioned an ad hoc committee to provide recommendations for the investigation, examination, and reporting of deaths in custody. Deaths in custody, whether occuring in jail/prison or during an altercation with law enforcement, is a complex issue and requires the forensic pathologist to be knowledgable and deliberative about his/her diagnosis. This paper provides recommendations for the forensic pathologist as it relates to 1) categorization of deaths in custody, 2) critical information required during investigation, 3) enhanced autopsy procedures, 4) guidance on death certification, 5) parameters for statistical reporting, and 6) release of information to the public. A uniform approach by medical examiners and coroners to the investigation and evaluation of deaths in custody is critical. The establishment of recommendations has the potential to ensure consistency and reliability to the definition, investigation, and certification of these cases. Such uniformity and consistency will instill confidence in the independence of the medical examiner/forensic pathologist/coroner by the criminal justice system, public health system, and community at large.